1994
DOI: 10.1210/jcem.78.5.8175974
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and renal effects of low dose brain natriuretic peptide infusion in man.

Abstract: We evaluated the effects of pathophysiological levels of human brain natriuretic peptide (BNP), a recently identified cardiac hormone with natriuretic activity, by determining the hemodynamic and renal responses to low dose infusion (4 pmol/kg.min for 1 h, from 1500-1600 h) of human synthetic BNP in five healthy volunteers in a randomized placebo-controlled crossover study. Compared to placebo, BNP induced significant increases in effective renal plasma flow (para-aminohippurate clearance), glomerular filtrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 24 publications
3
30
0
Order By: Relevance
“…Similarly, studies of BNP have come to conflicting conclusions about the effects on glomerular filtration rate (GFR) or renal plasma flow. [5][6][7] The extent of the renal effects of nesiritide when given in therapeutic doses to decompensated CHF patients is uncertain.…”
Section: See P 1514mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, studies of BNP have come to conflicting conclusions about the effects on glomerular filtration rate (GFR) or renal plasma flow. [5][6][7] The extent of the renal effects of nesiritide when given in therapeutic doses to decompensated CHF patients is uncertain.…”
Section: See P 1514mentioning
confidence: 99%
“…[11][12][13][14] Human studies that have demonstrated improved GFR have generally evaluated a small number of normal individuals. 5,15 Even these studies, however, have not necessarily demonstrated improved ERPF. 6 Nesiritide appears to exert hemodynamic effects in patients with both CHF and renal dysfunction (although the effects may be quantitatively different from those seen in normal individuals).…”
Section: Gfr and Erpfmentioning
confidence: 99%
“…Although most but not all studies in healthy humans reported that BNP infusion increases glomerular filtration rate, 1,[5][6][7] renal plasma flow has been found to decrease, 1,7 to increase, 5 or to remain unchanged. 3,8 Variations in the renovascular effects of BNP could be related to differences in BNP levels reached during the experiments, but it is equally possible that the renal changes are, in part, secondary to systemic effects.…”
mentioning
confidence: 95%
“…S ystemic infusion of brain natriuretic peptide (BNP) stimulates natriuresis and diuresis [1][2][3][4][5][6] and inhibits plasma renin activity [1][2][3]7,8 but has variable effects on the renal vasculature. Although most but not all studies in healthy humans reported that BNP infusion increases glomerular filtration rate, 1,[5][6][7] renal plasma flow has been found to decrease, 1,7 to increase, 5 or to remain unchanged.…”
mentioning
confidence: 99%
“…It was also found to have diuretic and natriuretic properties. 30 BNP (nesiritide) is well tolerated. Its most signifi cant adverse effect is dose-related hypotension, which occurs in 4%-5% of patients.…”
mentioning
confidence: 99%